2018
DOI: 10.1002/pds.4422
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuation and dose adjustment of metoprolol after metoprolol‐paroxetine/fluoxetine co‐prescription in Dutch elderly

Abstract: PurposeCo‐prescription of paroxetine/fluoxetine (a strong CYP2D6 inhibitor) in metoprolol (a CYP2D6 substrate) users is common, but data on the clinical consequences of this drug‐drug interaction are limited and inconclusive. Therefore, we assessed the effect of paroxetine/fluoxetine initiation on the existing treatment with metoprolol on the discontinuation and dose adjustment of metoprolol among elderly.MethodsWe performed a cohort study using the University of Groningen IADB.nl prescription database (www.IA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…Meanwhile, the control group consisted of metoprolol users without hospitalization and who were newly treated with the studied drugs (394 patients). The second study is a retrospective cohort study by Bahar et al using a prescription database (IADB.nl) among Dutch elderly (≥60 years) patients with metoprolol prescription (64 578 patients) who were co‐prescribed with paroxetine/fluoxetine (528 patients), with citalopram (673 patients), and with mirtazapine (625 patients) . No PK data were presented in these studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the control group consisted of metoprolol users without hospitalization and who were newly treated with the studied drugs (394 patients). The second study is a retrospective cohort study by Bahar et al using a prescription database (IADB.nl) among Dutch elderly (≥60 years) patients with metoprolol prescription (64 578 patients) who were co‐prescribed with paroxetine/fluoxetine (528 patients), with citalopram (673 patients), and with mirtazapine (625 patients) . No PK data were presented in these studies.…”
Section: Resultsmentioning
confidence: 99%
“…The authors explained that it might be caused by differences in the body mass index and the rate of CYP2D6 metabolic activity between men and women. However, the data regarding the latter is not clear [32].…”
Section: Discussionmentioning
confidence: 97%
“…However, it has been observed that coadministration of Metoprolol and Mirtazapine is safe with no clinically significant DDIs [ 83 ]. In fact, this lack of clinical adverse effects has been documented to such a degree that Mirtazapine has been used as the negative control in a case–control study of interactions between Metoprolol and selective serotonin reuptake inhibitors [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…We applied a retrospective inception cohort study (figure 1) using the University of Groningen’s prescription database IADB.nl that contains over 1.2 million dispensings from about 600 000 patients in 60 community pharmacies in the Netherlands since 1994 25 26. IADB.nl provided complete information including date of birth, gender, prescribed drug name, anatomical therapeutic chemical (ATC) codes, dispensing date, quantity dispensed and dose regimen 27.…”
Section: Methodsmentioning
confidence: 99%